Dobra kultury jako czynnik rozwoju dużych miast - Wieprow, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Culture properties may constitute an important factor in the agglomeration development. Significance of culture heritage shall mainly refer to monuments of different type enriching the quantity and the quality of cultural offer of the city, influencing the tourism development, establishing new job- positions at the same time increasing local budget's income. All kinds of monuments influence strongly the quality, beauty as well as advancement and image of agglomeration. They establish the level of city attractiveness as a place for settling down. Well-used cultural heritage shall be a constituent of creation process of higher life standards and social life development in the city.Development of culture properties market as well as constantly increasing interest in it result in tighter connection between the culture and tourism as well as an interest in culture influence on other areas (economy of the city, an element of symbol, atmosphere, and city extent). More frequently cultural activity turns to be a crucial factor of city strategy as well as its space arrangement schedule. Therefore, the influence of culture properties on the agglomeration development turns to be multi-aspectual. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 134-147